The Intermedia Books: a Concept of Book And Multimedia Integration for Remedial - Yogananta, Damar; Utanto, Yuli; Kustiono, Kustiono (Innovative Journal of Curriculum and Educational Technology, 2022)
The research and development of the Intermedia Book are motivated by the remedial implementation conditions of Indonesian lessons that have not been optimal. The preliminary research results that students need a book that can accommodate the remedial process by the learner's era. The concept of multimedia and book integration is a good solution for Indonesian remedial learning. The purpose of this research is to develop the Intermedia Book for remedial processes of Indonesian subjects. This research used the ten steps Borg & Gall model. From the ten steps Borg & Gall, the researcher modifies into three main steps: (1) preparation, (2) development, and (3) validation. The product of this research is the Intermedia Book of Indonesian Subject for VII grade students. The implication of this research is to bring multimedia products closer to learners through the intermedia book. This development becomes one of the techniques to increase the interactive learning process.